A wolf at the table : a memoir of my father - Burroughs, Augusten (New York : St. Martin's Press, 2008)
The author of "Running with Scissors" delves into new territory with his most personal and unexpected memoir yet. "A Wolf at the Table" is the story of Burroughs' relationship with his father, his stunning psychological cruelty, and the redemptive power of hope
Keywords: Burroughs, Augusten -- Family; Novelists, American -- 20th century -- Biography